Tuning the performance of vanadium redox flow batteries by modifying the structural defects of the carbon felt electrode - Dixon, Ditty; Babu, Deepu Joseph; Bhaskar, Aiswarya; Bruns, Hans-Michael; Schneider, Joerg J.; Scheiba, Frieder; Ehrenberg, Helmut (Beilstein Journal of Nanotechnology, 2019)
Polyacrylonitrile (PAN)-based carbon felt was subjected to N2-plasma treatment to increase the heteroatom defects and reactive edge sites as a method to increase the performance in vanadium redox flow batteries (VRFBs). N-doping in the felt was mainly in the form of pyrrolic and pyridinic nitrogen. Even though the amount of oxygen functional groups on the N2-plasma-treated sample was very low, the felt showed enhanced electrochemical performance for both V3+/V2+ as well as V5+/V4+ redox reactions. The result is highly significant as the pristine electrode with the same amount of oxygen functional groups showed significantly less activity for the V3+/V2+ redox reaction. Overall, the single-flow cell experiments with N2-plasma-treated felt showed superior performance compared to the pristine sample. Therefore, the enhanced performance observed for the N2-plasma-treated sample should be attributed to the increase in defects and edge sites. Thus, from the present study, it can be concluded that an alternate way to increase the performance of the VRFBs is to introduce specific defects such as N-doping/substitution or to increase the edge sites. In other words, defects induced in the carbon felt such as heteroatom doping are as beneficial as the presence of oxygen functional groups for the improved performance of VRFBs. Therefore, for an optimum performance of VRFBs, defects such as N-substitution as well as oxygen functionality should be tuned.
Keywords: carbon felt; defects; nitrogen plasma; vanadium redox flow battery (VRFB)

(untitled) - SkyllasKazacos, M.; Rychcik, M.; Robins, R. G.; Fane, A. G.; Green, M. A. (J. Electrochem. Soc., 1986)

(untitled) - Tang, A.; Bao, J.; Skyllas-Kazacos, M. (J. Power Sources, 2011)

(untitled) - Shah, A. A.; Al-Fetlawi, H.; Walsh, F. C. (Electrochim. Acta, 2010)

(untitled) - Whitehead, A. H.; Harrer, M. (J. Power Sources, 2013)

(untitled) - Wang, L.; Zhang, H.; Cao, G.; Zhang, W.; Zhao, H.; Yang, Y. (Electrochim. Acta, 2015)

(untitled) - Langner, J.; Bruns, M.; Dixon, D.; Nefedov, A.; Wöll, C.; Scheiba, F.; Ehrenberg, H.; Roth, C.; Melke, J. (J. Power Sources, 2016)

(untitled) - Dixon, D.; Babu, D. J.; Langner, J.; Bruns, M.; Pfaffmann, L.; Bhaskar, A.; Schneider, J. J.; Scheiba, F.; Ehrenberg, H. (J. Power Sources, 2016)

(untitled) - Agar, E.; Dennison, C. R.; Knehr, K. W.; Kumbur, E. C. (J. Power Sources, 2013)

(untitled) - Derr, I.; Bruns, M.; Langner, J.; Fetyan, A.; Melke, J.; Roth, C. (J. Power Sources, 2016)

(untitled) - Derr, I.; Przyrembel, D.; Schweer, J.; Fetyan, A.; Langner, J.; Melke, J.; Weinelt, M.; Roth, C. (Electrochim. Acta, 2017)

(untitled) - Estevez, L.; Reed, D.; Nie, Z.; Schwarz, A. M.; Nandasiri, M. I.; Kizewski, J. P.; Wang, W.; Thomsen, E.; Liu, J.; Zhang, J.-G.; Sprenkle, V.; Li, B. (ChemSusChem, 2016)

(untitled) - Schweiss, R.; Pritzl, A.; Meiser, C. (J. Electrochem. Soc., 2016)

(untitled) - Boukhvalov, D. W.; Katsnelson, M. I. (Nano Lett., 2008)

(untitled) - Banhart, F.; Kotakoski, J.; Krasheninnikov, A. V. (ACS Nano, 2011)

(untitled) - Wang, S.; Zhao, X.; Cochell, T.; Manthiram, A. (J. Phys. Chem. Lett., 2012)

(untitled) - He, Z.; Shi, L.; Shen, J.; He, Z.; Liu, S. (Int. J. Energy Res., 2015)

(untitled) - Ferrari, A. C. (Solid State Commun., 2007)

(untitled) - Pimenta, M. A.; Dresselhaus, G.; Dresselhaus, M. S.; Cançado, L. G.; Jorio, A.; Saito, R. (Phys. Chem. Chem. Phys., 2007)

(untitled) - Ouyang, B.; Zhang, Y.; Wang, Y.; Zhang, Z.; Fan, H. J.; Rawat, R. S. (J. Mater. Chem. A, 2016)

(untitled) - Babu, D. J.; Bruns, M.; Schneider, R.; Gerthsen, D.; Schneider, J. J. (J. Phys. Chem. C, 2017)

(untitled) - Kiuchi, H.; Shibuya, R.; Kondo, T.; Nakamura, J.; Niwa, H.; Miyawaki, J.; Kawai, M.; Oshima, M.; Harada, Y. (Nanoscale Res. Lett., 2016)

(untitled) - Nevidomskyy, A. H.; Csányi, G.; Payne, M. C. (Phys. Rev. Lett., 2003)

(untitled) - Rabbow, T. J.; Trampert, M.; Pokorny, P.; Binder, P.; Whitehead, A. H. (Electrochim. Acta, 2015)

(untitled) - Xu, A.; Shi, L.; Zeng, L.; Zhao, T. S. (Electrochim. Acta, 2019)

(untitled) - Chen, P.; Fryling, M. A.; McCreery, R. L. (Anal. Chem. (Washington, DC, U. S.), 1995)

Electrochemical Equilibria in Aqueous Solutions - Pourbaix, M. (Pergamon Press, 1966)

(untitled) - Nose, M.; Kinumoto, T.; Choo, H.-S.; Miyazaki, K.; Abe, T.; Ogumi, Z. (Fuel Cells, 2009)

(untitled) - Babu, D. J.; Yadav, S.; Heinlein, T.; Cherkashinin, G.; Schneider, J. J. (J. Phys. Chem. C, 2014)

(untitled) - Parry, K. L.; Shard, A. G.; Short, R. D.; White, R. G.; Whittle, J. D.; Wright, A. (Surf. Interface Anal., 2006)

(untitled) - Tanuma, S.; Powell, C. J.; Penn, D. R. (Surf. Interface Anal., 2011)

(untitled) - Fink, H.; Friedl, J.; Stimming, U. (J. Phys. Chem. C, 2016)